Pengembangan E-Modul Dengan Pendekatan Problem Solving pada Pokok Bahasan Bangun Ruang Sisi Datar - Dewi, Fauziyyah Kristanti Monica; Mutaqin, Anwar; Rahayu, Ilmiyati (Media Pendidikan Matematika, 2023)
The rapid development of Science and Technology (IPTEK) can be used as an alternative way to develop the learning process. one example of learning that utilizes technology is teaching materials. The output of this developed product is an e-module that can be operated through a web browser or .exe file. The purpose of this study is to determine the validity, practicality, and effectiveness of e-modules with a prolem solving approach on the subject of flat-sided space building in class VIII junior high school. The type of research used is R&D (Research and Development) which refers to the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). This research was conducted at SMP Negeri 2 Balaraja consisting of 35 students in class VIII F in the 2022/2023 school year. The instruments used were interview sheets, material expert validation questionnaires, media expert validation questionnaires, teacher response questionnaires, student response questionnaires, and learning outcomes tests. The data analysis technique was carried out quantitatively descriptive and qualitative descriptive. Based on the results of the development carried out, the percentage of assessments from material expert validators was 85.18%, media experts were 86.28%, educator responses were 93.32%, student responses were 91.91%, and the completeness of student learning outcomes tests was 85.7%. So, it can be concluded that the development of e-modules with a problem solving approach on the subject of flat-sided spaces can be declared valid, practical, and effective in the learning process